Enhanced Secondary- and Hormone Metabolism in Leaves of Arbuscular MycorrhizalMedicago truncatula - Adolfsson, Lisa; Nziengui, Hugues; Abreu, Ilka N; Šimura, Jan; Beebo, Azeez; Herdean, Andrei; Aboalizadeh, Jila; Široká, Jitka; Moritz, Thomas; Novák, Ondřej; Ljung, Karin; Schoefs, Benoît; et al. (Plant physiology, 2017)
Arbuscular mycorrhizas (AM) are the most common symbiotic associations between a plant's root compartment and fungi. They provide nutritional benefit (mostly inorganic phosphate [Pi]), leading to improved growth, and nonnutritional benefits, including defense responses to environmental cues throughout the host plant, which, in return, delivers carbohydrates to the symbiont. However, how transcriptional and metabolic changes occurring in leaves of AM plants differ from those induced by Pifertilization is poorly understood. We investigated systemic changes in the leaves of mycorrhizedMedicago truncatulain conditions with no improved Pistatus and compared them with those induced by high-Pitreatment in nonmycorrhized plants. Microarray-based genome-wide profiling indicated up-regulation by mycorrhization of genes involved in flavonoid, terpenoid, jasmonic acid (JA), and abscisic acid (ABA) biosynthesis as well as enhanced expression ofMYC2, the master regulator of JA-dependent responses. Accordingly, total anthocyanins and flavonoids increased, and most flavonoid species were enriched in AM leaves. Both the AM and Pitreatments corepressed iron homeostasis genes, resulting in lower levels of available iron in leaves. In addition, higher levels of cytokinins were found in leaves of AM- and Pi-treated plants, whereas the level of ABA was increased specifically in AM leaves. Foliar treatment of nonmycorrhized plants with either ABA or JA induced the up-regulation ofMYC2, but only JA also induced the up-regulation of flavonoid and terpenoid biosynthetic genes. Based on these results, we propose that mycorrhization and Pifertilization share cytokinin-mediated improved shoot growth, whereas enhanced ABA biosynthesis and JA-regulated flavonoid and terpenoid biosynthesis in leaves are specific to mycorrhization.
Keywords: Terpenes; Mycorrhizae; Plant Growth Regulators; flavonoidy; upregulace; Cyclopentanes; oxylipiny; Medicago truncatula; sekundární metabolismus; regulátory růstu rostlin; kyselina abscisová; Plant Leaves; Abscisic Acid; Secondary Metabolism; rostlinné proteiny; listy rostlin; symbióza; Up-Regulation; Gene Expression Regulation, Plant; fosfáty; Symbiosis; mykorhiza; Flavonoids; Oxylipins; cyklopentany; Phosphates; regulace genové exprese u rostlin; Glomeromycota; terpeny; Plant Proteins